Animal Farm: Considerations in Animal Gastrointestinal Physiology and Relevance to Drug Delivery in Humans. Issue 9 (24th February 2015) - Hatton, Grace B.; Yadav, Vipul; Basit, Abdul W.; Merchant, Hamid A.; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; Yu, Lawrence X.
<x xml:space="preserve">Abstract</x> "All animals are equal, but some are more equal than others" was the illustrious quote derived from British writer George Orwell's famed work, Animal Farm. Extending beyond the remit of political allegory, however, this statement would appear to hold true for the selection of appropriate animal models to simulate human physiology in preclinical studies. There remain definite gaps in our current knowledge with respect to animal physiology, notably those of intra‐ and inter‐species differences in gastrointestinal (GI) function, which may affect oral drug delivery and absorption. Factors such as cost and availability have often influenced the choice of animal species without clear justification for their similarity to humans, and lack of standardization in techniques employed in past studies using various animals may also have contributed to the generation of contradictory results. As it stands, attempts to identify a single animal species as appropriately representative of human physiology and which may able to adequately simulate human in vivo conditions are limited. In this review, we have compiled and critically reviewed data from numerous studies of GI anatomy and physiology of various animal species commonly used in drug delivery modeling, commenting on the appropriateness of these animals for in vivo comparison and extrapolation to humans. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2747–2776, 2015